Letters to the Editor: A Collection of Experiences - Galindo Salomón, Andrea Joannna; Perez Cardozo, Dayro Fabian; Murillo Villa, Mayra Lorena; Setina Rubiano, Juan Felipe; Montes Rivas, Andrés David; Ibañez Galvis, María José; Rico Artunduaga, Reinaldo Andrés; Miranda Ordoñez, Cristian Fernando; Prieto Wilches, Erika Alexandra; Tiria Sotelo, Yohan Sneider; Vargas Arévalo, María Camila; Vásquez Guarnizo, Jhonatan (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Students, teachers, and staff express their experiences and thoughts about teaching, learning, and living during the current pandemic.